Tiptoeing the line: towards the development of an international school drama curriculum for social justice. - James, Corin (Trinity College (Dublin, Ireland). School of Education, 2021)
2020 has been a difficult year: events such as the COVID-19 pandemic and the Black Lives Matter protests have highlighted some of the inequities that exist in the world. For those working in education, such global contexts create tensions between the need to ensure students are academically successful and a desire to empower students to work for a fairer, more equitable world. This study is a piece of qualitative secondary research which takes the form of a traditional literature review. It examines the extent to which an international school drama curriculum could promote social justice while also enabling middle school students to develop their skills as drama students. The literature reviewed is drawn from the discourses of social justice education, elite education, international school studies and drama in education. The first part of the study examines the literature related to social justice education, elite education and international schools. This leads to the creation of a framework for social justice education in international schools. This framework is then used as a basis for the exploration of literature related to drama in education. There is a focus on the tensions between learning through drama about the world and learning about drama as an art form, as well as an examination of some of the main features of process drama. A model is proposed for drama teaching that might fulfil the social justice framework. This model allows teachers to shift the primary focus from learning about drama to learning through drama, depending on the learning objectives. It adopts a hybrid form of process drama that uses an episodic structure to enable new understandings of the issue being explored. Students work in role to experience thinking from within different discourses, while the teacher manages levels of immersion and distance. Students reflect on both the issues explored in the drama and the ways in which the art form is being used to generate moments of significant experience. The findings of this study are inevitably tentative: they exist at the level of theory without being tested in any practical manner. The conclusion therefore recommends that the model for drama is put into practice in order to inform a critical evaluation of the theory. This could lead to the development of a praxis of drama teaching oriented towards social justice in an international school context.
Keywords: Drama in Education; Education